TSC2 pathogenic variants are predictive of severe clinical manifestations in TSC infants: results of the EPISTOP study - Ogórek, Barbara; Hamieh, Lana; Hulshof, Hanna M.; Lasseter, Kathryn; Klonowska, Katarzyna; Kuijf, Hugo; Moavero, Romina; Hertzberg, Christoph; Weschke, Bernhard; Riney, Kate; Feucht, Martha; Scholl, Theresa; et al. (Genetics in medicine, 2020)
Purpose To perform comprehensive genotyping of TSC1 and TSC2 in a cohort of 94 infants with tuberous sclerosis complex (TSC) and correlate with clinical manifestations. Methods Infants were enrolled at age <4 months, and subject to intensive clinical monitoring including electroencephalography (EEG), brain magnetic resonance imaging (MRI), and neuropsychological assessment. Targeted massively parallel sequencing (MPS), genome sequencing, and multiplex ligation-dependent probe amplification (MLPA) were used for variant detection in TSC1 / TSC2 . Results Pathogenic variants in TSC1 or TSC2 were identified in 93 of 94 (99%) subjects, with 23 in TSC1 and 70 in TSC2 . Nine (10%) subjects had mosaicism. Eight of 24 clinical features assessed at age 2 years were significantly less frequent in those with TSC1 versus TSC2 variants including cortical tubers, hypomelanotic macules, facial angiofibroma, renal cysts, drug-resistant epilepsy, developmental delay, subependymal giant cell astrocytoma, and median seizure-free survival. Additionally, quantitative brain MRI analysis showed a marked difference in tuber and subependymal nodule/giant cell astrocytoma volume for TSC1 versus TSC2 . Conclusion TSC2 pathogenic variants are associated with a more severe clinical phenotype than mosaic TSC2 or TSC1 variants in TSC infants. Early assessment of gene variant status and mosaicism might have benefit for clinical management in infants and young children with TSC.